Parcours-travail et cancers professionnels. Recherche-action en Seine Saint Denis (France) - Annie Thébaud-Mony; Laura Boujasson; Michael Levy; Catherine Lepetit; Parvine Goulimaly; Hélène Carteron; Michèle Vincenti (Perspectives Interdisciplinaires sur le Travail et la Santé)
In the field of occupational cancer, toxicology and epidemiology have produced a substantial amount of data that have been used to identify the causal relationship and statistical correlation between toxic substances and some types of cancer. However, little information is available on the social reality of work and occupational exposure to carcinogenic agents. A multidisciplinary and proactive scientific study, based on interviews with incident cases, was undertaken in a highly industrialized suburb of Paris. The preliminary study, carried out in the Avicenne hospital (attached to the University of Paris13, Bobigny), allowed us to build methodological tools. Our goal was to collect qualitative data on occupational exposure to carcinogenic agents in the job histories of new patients living in Seine Saint Denis.In this paper, we present out theoretical and methodological approach, along with some results. Exposure to carcinogens was very common in our study group. We identified different types of job histories involving a combination of blue-collar work and occupational exposure to carcinogens. It was then possible to differentiate between cases due to past occupational exposure to carcinogenic agents and those involving workers who are still exposed in their current positions. Where exposure occurs, there is clearly an urgent need for preventive strategies to avoid future cases of cancer. Through the study, we were able to register cumulated and multiple exposure throughout a worker’s job history and to qualify that exposure. The job history study is not necessarily the only way of identifying whether or not patients have been exposed to carcinogenic agents, but it is a way of developing two other kinds of knowledge, namely how the exposure histories fit into an individual and collective history, both spatially and temporally, and how to recognize and compensate for occupational disease procedures - in other words, to see how the compensation system rules are applied and how they can be changed to suit the specific situation of occupational cancer victims.